Institut samoprijave v slovenski davčni ureditvi in praksi - Špilar, Marjan (Podjetje in delo, 2018)
In this article, the author examines the institute of tax self-declaration which is the subject of our general tax legislation in the Tax Procedure Act and constitutes a certain balance to strict tax regulations. Tax self-declaration is a special material tax institute, primarily designed to entice taxpayers to meet their tax liabilities, which they were not able to meet or have only partially done so, for whatever reason, and in return they receive a remission from penalties that normally apply in such cases. The fundamental difference between a self-declaration and other tax institutes that enable tax liabilities to be met subsequently, is that a self-declaration is permitted even when the taxpayers deliberately did not meet their tax liabilities, or have done so incorrectly, and have later changed their minds. The compensation for a self-declaration is the remission of penalties which does not eliminate the existence of the offence, but it does eliminate the penalty for it. The taxpayer must fulfil his real tax obligations, when he files his self-declaration, increased by the statutory interest, otherwise it cannot take effect. In the Slovenian tax legislation, self-declaration is set out under the Tax Procedure Act in two parts. The first general part of the act governs the relatively strict statutory conditions and ways of submitting tax declarations or tax returns based on a self-declaration. Conditions for a remission of penalties in the case of self-declarations are set out in the penalty clauses of the act. A self-declaration that enables the offender a remission of the provided penalty is not permitted for all tax offences, but merely for those that are linked to meeting lax liabilities and are set out under the Tax Procedure Act. Tax self-declaration applies only to offences that occurred because the taxpayer was too late in submitting his tax declaration or tax return, or because he did not pay enough tax. The institute of self-declaration is also present in the Slovenian legal system in the Value Added Tax Act and does not differ from a self-declaration under the Tax Procedure Act, it is merely an alternative way of tax compliance through value added tax returns. The tax procedure by self-declaration always begins at the request of the taxpayer, who subsequently files a tax declaration or a tax return that was submitted to late, in which he states the unpaid taxes or the shortfall in the taxes paid. The taxpayer must file the overdue tax declaration or tax return as a self-declaration within the provided deadline and only once for the same tax liability. A self-declaration is filed in due time, if it is filed no later than before the start of tax inspection and before the tax adjustment notice is issued or before the administrative proceeding for the offence or the criminal proceeding starts. The relevant tax authority shall reject the self-declaration of any taxpayer for tax that does not meet the applicable legal conditions, and in the subsequent procedure regard the tax declaration or return as filed after the provided legal deadline. The legislator, state and state authorities, responsible for the collection of duties, consider self-declaration a very important administrative institute. The tax authorities' data show that taxpayers often make use of self-declaration as a way to subsequently meet their tax liabilities and in doing so they contribute a relatively large amount of public revenue to the public budget. The legislator also often undermines the institute of self-declaration in light of protecting the public interest in collecting duties, which naturally does not benefit legal certainty in the field of taxation. Thereby questions and dilemmas arise within the regulatory framework of self-declaration, showing shortfalls within the standardisation of the institute and consequently the possibility of arbitrary decision making and unequal treatment of taxpayers in practice. In this article, the author underlines some of these questions and dilemmas and presents a comparative view of this institute in Austria and Germany.
Keywords: davčna obveznost; davčna samoprijava; davčni postopek; davčni zavezanec; posebni instituti davčnega postopka